Aggressiveness and social skills in elementary school children in the I.E. 10020, Zaña 2016 - Hernández Quispe, Estrellita (2017)
The present study entitled "Aggressiveness and social skills in elementary school children of Educational Institution 10020, Zaña 2016", aims to verify the significance level between the aggressiveness and social skills in students. The objective is to determine the level of connection between aggressiveness and social skills. The type of research is descriptive correlational, with non-experimental design. The population is made up of 410 students and the sample was established by children whose ages are between 10 and 12 years, 52 students were taken into account by the probabilistic sample. In conclusion, there is no connection between aggressiveness and social skills.